1990
DOI: 10.3109/02713689008999572
|View full text |Cite
|
Sign up to set email alerts
|

Tumor destruction by intermediate level hyperthermia

Abstract: The tumoricidal effect of hyperthermia was studied in Greene's amelanotic hamster melanoma transplanted into the anterior chamber of rabbit eyes. To achieve optimal depth penetration, hyperthermia was induced with near infrared light of 820-870 nm, during 15 minutes, at a beam diameter of 2.5-6.0 mm resulting in an intermediate level hyperthermia of 45-60 degrees C. At 45 degrees C no tumor destruction occurred, at 50 degrees C the effect varied from no destruction to total thickness tumor destruction. At 55-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

1991
1991
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 18 publications
1
14
0
3
Order By: Relevance
“…At temperatures higher than 60 ~ high range hyperthermia, a white coagulation effect develops which reduces uptake of radiation [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At temperatures higher than 60 ~ high range hyperthermia, a white coagulation effect develops which reduces uptake of radiation [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…millimeters, and a wavelength between 700 and 900 nm [5]. Several studies have demonstrated a remarkable necrosis depth in non-ocular tissue after treatment by near infrared irradiation [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Heat influence on melanoma has been investigated very detailed in the field of TTT of choroidal melanomas [25,26,27,28,29]. TTT can be used as single treatment or in combination with brachytherapy.…”
Section: Sclera Infiltration By Melanoma Cellsmentioning
confidence: 99%
“…Thermotherapy uses the principle of intermediate level hyperthermia in the range of 45-608C. Nuijs-Beems et al [27] found this temperature range to be sufficient for destruction of cells, when applied for more than 1 minute up to 10 minutes. Thermotherapy is thought to cause tissue effects some days after application.…”
Section: Sclera Infiltration By Melanoma Cellsmentioning
confidence: 99%
“…Nuijs-Beems e col. (4) e Jornee-de-Korvwer e col. (5)(6)(7) foram os primeiros a relatar a utilização da hipertermia como tratamento primário e único em animais. Tanto Oostherhuis e col. (8) como Shields e col. (9)(10) obtiveram sucesso no tratamento de melanomas pequenos utilizando este método como forma única de tratamento em respectivamente 3, 17 e 100 pacientes.…”
Section: Introductionunclassified